ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, DIFERENSIASI PRODUK, KUALITAS LAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Konsumen Larissa Aesthetic Center Semarang) - Hanesty Purbarani, Vidya; Budi Santoso, Suryono (Diponegoro Journal of Management, 2013)
This research is motivated by the increasing growth of beauty clinics and offervarious range of benefits for fulfilling the society’ needs especially women in field of beauty and skin health. Larissa Aesthetic Center is one of the beauty clinics which try to meet those needs by featuring the use of natural raw materials. This research aimed to analyze the effects of perception of price, product quality, product differentiation, quality of service and promotion on purchase decisions in Larissa Aesthetic Center Semarang.By using accidental sampling technique, questionnaires is given toward 100 respondents. Then, the result of questionnaires processed by using SPSS software to obtain calculation of quantitative analysis such as the validity and reliability test, clasic assumptions test, two-stages regression analysis with Goodness of Fit test (F-test), degree of determinant test (R2), parsial significant test (t-test) and also to porduce a regression equation.Results of this research showed that perception of price, product quality, product differentiation, service quality and promotions have positive impact to purchasing decicion. The most significant variable to purchasing decicion is promotion and the less significant is product quality. This research also found that there are unique customer characteristics in where customer prefer cheaper price but then questioned the quality gained from the cheap price. The customer also like that Larissa Aesthetic Center products which made from natural ingredients but also dissatisfied by its effects which not instantly seen.